2015
DOI: 10.1111/mec.13202
|View full text |Cite
|
Sign up to set email alerts
|

Localization of quantitative trait loci for diapause and other photoperiodically regulated life history traits important in adaptation to seasonally varying environments

Abstract: Seasonally changing environments at high latitudes present great challenges for the reproduction and survival of insects, and photoperiodic cues play an important role in helping them to synchronize their life cycle with prevalent and forthcoming conditions. We have mapped quantitative trait loci (QTL) responsible for the photoperiodic regulation of four life history traits, female reproductive diapause, cold tolerance, egg-to-eclosion development time and juvenile body weight in Drosophila montana strains fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Interestingly, conspecific D. montana populations have been shown to diverge in traits that play a role in ecological adaptation (e.g., Lankinen et al. 2013 ; Tyukmaeva et al. 2015 ), male sexual cues and female preferences (e.g., Klappert et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, conspecific D. montana populations have been shown to diverge in traits that play a role in ecological adaptation (e.g., Lankinen et al. 2013 ; Tyukmaeva et al. 2015 ), male sexual cues and female preferences (e.g., Klappert et al.…”
Section: Introductionmentioning
confidence: 99%
“…Information on potential candidate genomic regions and genes for traits involved in cold adaptation and sexual selection has been accumulated through QTL ( Schäfer et al. 2010 ; Tyukmaeva et al. 2015 ), microarray ( Vesala et al.…”
Section: Introductionmentioning
confidence: 99%
“…Machado et al (2016) performed a longitudinal study of Drosophila collected at differing latitudes during a two year time span and compared physiological traits of two different species: D. melanogaster and D. simulans . Other studies have gone further by identifying quantitative trait loci (QTL) for body size and cold tolerance traits involved in adaptation to seasonally varying environments (Tyukmaeva et al 2015; Hangartner et al 2015). Gerken et al (2015) found substantial heritable variation in both short-term and long-term acclimation.…”
mentioning
confidence: 99%
“…Genetic basis of diapause expression in insects is emerging as an important facet of recent studies on seasonal polyphenism. Key molecular processes governing diapause have been identified in numerous species from various clades (e.g., Mori et al, 2007;Tyukmaeva et al, 2015;Zhao et al, 2016). The regulation of seasonal photoperiodism is strongly related to the system governing circadian rhythms in insects (B€ unning, 1960;Goto, 2013;Dolezel, 2015).…”
Section: Genetics Of Diapausementioning
confidence: 99%